Effect of Crude Oil Polluted Water on the Haematology of Cockerel Reared under Intensive System - Akporhuarho , P.O. (International Journal of Poultry Science, 2011)
This study was designed to investigate the effect of polluted water on the Hematological indices of cockerels fed with polluted water at 5 ml, 10 ml and 15 ml of crude oil. The results showed that there was a significant difference (p<0.05) in the Red Blood Cell (RBC) and White Blood Cell (WBC). Also, there was a significant difference (p<0.05) in the Mean Corpuscular Hemoglobin (MCH) and Mean Corpuscular Volume (MCV). There was no significant difference (p<0.05) in the Packed Cell Volume (PCV), Plasma Protein (P.P), Hemoglobin Concentration of Blood (HBC) and Mean Corpuscular Hemoglobin Count (MCHC). The significant reduction in RBC and WBC indicate hemolytic anaemia and exposes the birds to high risk of infections. This is due to injurious effect of the toxic components of the crude oil.